Design study for a 5 GW base load power drawn from satellite solar power station - Kumar D.; Chaudhary K. (My University, 2025)
In this work, satellite solar power station as base load plant model estimated analysis has performed. SSPS base load power plant for 5 GW model has investigated, and its feasibility prospects are studied. The SSPS essential components sizes have estimated for 5 GW power productions on the ground. A microwave power transmission with high beam efficiency approach is adopted in this work and beam energy effect on transmitting antenna size has examined. © Springer Nature Singapore Pte Ltd. 2018.